Desenvolvimento de barra magnética com revestimento monolítico de celulose para extração sortiva (SBSE) de glicerol em biodiesel - Martins, Pablo Henrique Silva (2023)
The transesterification of vegetable oil with short-chain alcohols results in biodiesel and glycerol as a co-product. After purification, the maximum content of free glycerol in biodiesel must not exceed 0.02 % (m/m) since its presence can clog the injection nozzle, release toxic vapors during combustion and cause damage to the engine. The glycerol content is an essential biofuel quality parameter. The official methods to determine the free glycerol content in biodiesel employ gas chromatography with flame ionization detection, requiring derivatizing reagents, internal standards, and limited instrumental conditions. In this proposal, we developed an alternative method for determining free glycerol in biodiesel that is simpler, sustainable, economical, and accessible to analysis laboratories. The methodology was based on glycerol extraction from biodiesel using a lab-made stir bar sorptive extraction (SBSE) and high-performance liquid chromatography with refractive index detection as an analytical technique. The sorptive stir-bar was prepared by coating neodymium magnets with monolithic cellulose, synthesized by the non solvent-induced phase separation method. We produced monoliths using commercial cellulose acetate, which was converted into cellulose by alkaline hydrolysis. The cellulose monolith was confirmed by the disappearance of acetate group signs in infrared spectroscopy and by the thermal properties of the monoliths by differential scanning calorimetry. The monoliths showed a hierarchically porous structure by scanning electron microscopy. Glycerol extraction from the fortified methyl oleate was optimized using the monolithic cellulose stir bars, obtaining an adsorption time of 60 min and a desorption time of 15 min, a temperature of 70 °C, water as a desorption solvent and bar length of stirring of 10 × 5 mm, resulting in a recovery rate of 93.6 ± 2.1 % (m/m) of glycerol. The proposed methodology was validated, resulting in limit of detection of 6.6 × 10-5 % (m/m) and limit of quantification of 2.9 × 10-4 % (m/m), good linearity, and high response sensitivity analytics. The results for determining free glycerol in biodiesel were comparable to the AOCS ca. 14-56 with the advantage of requiring few steps, low manipulation by the analyst, low cost, and not using any chemical reagent harmful to the environment, being fully compatible with the principles of sustainability.